AKTUALISASI NILAI MISI DALAM DINAMIKA BUDAYA PADA KELUARGA KRISTEN DI MENTAWAI: Indonesia - Malik Malik; Mesal Mesal; Hasahatan Hutahaean; Immerius Sakerebau (Manna Rafflesia, 2023)
This study discusses the importance of involving all congregation members in carrying out missions. The involvement of church members begins with the Christian family knowing the values of the mission. This is inseparable from how Christian leaders apply it in ministry. The purpose of the study was to explain the application of mission values in Christian families in Mentawai, by considering the condition of diversity that continues to grow in culture, religion, and tribe in Mentawai, West Sumatra. The method used is qualitative by collecting data from the literature. The results of the study found that the application of mission values in the Christian family can be made by being a bearer of good news, being a congregation of disciples, being a congregation that grows in teaching, and being a congregation that supports missions. The diversity of cultures, religions, and tribes in Mentawai can trigger the enthusiasm and persistence of the Church, both GKPM and other churches that serve there.